A National Vision for Land Use Planning in the United States - Eric G. Darracq; Jeffrey J. Brooks; Andrea K. Darracq (Land)
The time is nigh to organize the physical landscapes of the United States under a unified land use policy and planning framework. As human populations have steadily grown, so has the urgency for agencies to plan for land uses at broader scales to overcome continued jurisdictional fragmentation and achieve sustainable and environmentally just landscapes. This paper introduces a vision, conceptual approach, and implementation strategy that applies ecoregions and proposes a unified framework for land use planning and regulation in the United States. The Sustainable Ecoregion Program (SEP) is designed to enable local landowners; public stakeholders; other land users; and state, regional, tribal, and national natural resource professionals to set and achieve future desired conditions for sustainable land uses across landscapes. The objective is to outline a comprehensive and sustainably just solution to the recurring problem of managing conflicting land uses in the face of continued degradation and multiple land tenure systems. The SEP will determine how much of the physical landscape will go to developed, agricultural, and natural landcover types. The framework includes recognition of level III ecoregions as primary boundaries, proposed secondary boundaries and shapes to enhance connectivity and movement across landscapes, a proposed structure for the environmental governance and co-management of landscapes, and definitions of physical landscape types. The benefits and challenges of the SEP are discussed. The outcomes of the SEP include ecological integrity, sustainable land use management, deliberative democracy, just sustainability, and improved quality of life for residents of the United States.